2008
DOI: 10.1007/s11270-008-9826-5
|View full text |Cite
|
Sign up to set email alerts
|

The Odd–Even Behaviour of Dicarboxylic Acids Solubility in the Atmospheric Aerosols

Abstract: The solubility and the enthalpy of dicarboxylic acids have been determined in water at intervals between 278.5 and 543.5 K. At 298.15 K, the values derived were: Δ sol H m (m=1.33 mol kg −1 )=29.80 kJ mol −1 for oxalic acid; Δ sol H m (m=16.03 mol kg −1 )= 12.82 kJ mol −1 for malonic acid; Δ sol H m (m=0.75 mol kg −1 )=28.20 kJ mol −1 for succinic acid; Δ sol H m (m=8.77 mol kg −1 )=48.01 kJ mol −1 and Δ sol H m (m= 0.17 mol kg −1 )=40.30 kJ mol −1 for glutaric and adipic acid respectively. The solubility valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 40 publications
3
10
1
Order By: Relevance
“…It is evident from the figure that the domain of one-phase ME displays a "nosed-shaped" region. Similar "nose-shaped" micellar region were observed by Jeongt and co-workers [10], and Rozaini and Brimblecombe [11] for nonionic surfactant-oil-water ternary systems.…”
Section: Resultssupporting
confidence: 83%
“…It is evident from the figure that the domain of one-phase ME displays a "nosed-shaped" region. Similar "nose-shaped" micellar region were observed by Jeongt and co-workers [10], and Rozaini and Brimblecombe [11] for nonionic surfactant-oil-water ternary systems.…”
Section: Resultssupporting
confidence: 83%
“…Published values of solubility of the dicarboxylic acids are presented as function of the number of carbons in sodium dicarboxylate compounds in figure 7. A number of previous authors have observed this noticeable odd-even effect with dicarboxylic acid solubility [11][12][13].…”
Section: Resultsmentioning
confidence: 76%
“…These that appear as our results tabulated within figures 2 to 6. Solubility is plotted as the logarithm of the solubility in molal units (ln m vs 1/T) as this is preferable as the slope of the curve is related to the molar enthalpy of dissolution [13].…”
Section: Solubility Determinationmentioning
confidence: 99%
“…Although a strong contrast was found between the carbonaceous inclusion and its surrounding, a small but significant absorption is observed in the residual part of the particle. The solubility of adipic acid in pure water is low, 21 g/l (Rozaini & Brimblecombe, 2009), so that dissolved adipic acid could not significantly contribute to absorption. It is therefore likely that a thicker layer of adipic acid on top or underneath the solution is responsible for absorption there.…”
Section: Morphological Studies On Adipic Acid/ammonium Sulfate Mixturesmentioning
confidence: 99%
“…Such dicarboxylic acids have been identified in ambient aerosol particles whereby also adipic acid was found to be present in atmospheric aerosols (Ray & McDow, 2005). The adipic acid is known to be a poorly soluble organic compound in water (Rozaini & Brimblecombe, 2009). The hygroscopic properties of the mixture with ammonium sulfate were already investigated using HTDMA/TDMA and EDB (Hameri et al, 2002;Sjogren et al, 2007).…”
mentioning
confidence: 99%